Impact of free delivery policy on utilization of maternal health services in county referral hospitals in Kenya - John Njuguna; Njoroge Kamau; Charles Muruka (BMC Health Services Research, 2017)
Abstract Background Kenya has a high maternal mortality rate. Provision of skilled delivery plays a major role in reducing maternal mortality. Cost is a hindrance to the utilization of skilled delivery. The Government of Kenya introduced a policy of free delivery services in government facilities beginning June 2013. We sought to determine the impact of this intervention on facility based deliveries in Kenya. Methods We compared deliveries and antenatal attendance in 47 county referral hospitals and 30 low cost private hospitals not participating in the free delivery policy for 2013 and 2014 respectively. The data was extracted from the Kenya Health Information System. Multiple regression was done to assess factors influencing increase in number of deliveries among the county referral hospitals. Results The number of deliveries and antenatal attendance increased by 26.8% and 16.2% in county referral hospitals and decreased by 11.9% and 5.4% respectively in low cost private hospitals. Increase in deliveries among county referral hospitals was influenced by population size of county and type of county referral hospital. Counties with level 5 hospitals recorded more deliveries compared to those with level 4 hospitals. Conclusion This intervention increased the number of facility based deliveries. Policy makers may consider incorporating low cost private hospitals so as to increase the coverage of this intervention.